2019
DOI: 10.1177/1526602819860801
|View full text |Cite
|
Sign up to set email alerts
|

Homemade Candy Plug Using a Zenith Alpha Thoracic Stent-Graft for False Lumen Distal Occlusion in Acute-on-Chronic Type B Aortic Dissection

Abstract: Purpose: To report a candy-plug technique using a Zenith Alpha stent-graft to occlude the distal false lumen in a patient with a complicated chronic type B aortic dissection. Case Report: A 50-year-old male smoker presented with chest pain due to rapidly growing complicated chronic type B aortic dissection. Computed tomography angiography (CTA) showed the dissection extending from distal to the origin of the left subclavian artery (LSA) down to the left femoral artery. There was fusiform aneurysmal dilatation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Treatment strategies in chronic aortic dissection should include occlusion of the FL. 4,[8][9][10][11][12] This early experience with the next-generation CP showed that positioning of the device in the FL is feasible, with minimal morbidity and mortality and a high rate of complete FL backflow cessation on the final angiogram and postoperative CTA. Compared with the earlier generation, the CP II is tubular and has no midsection, which creates a longer sealing zone.…”
Section: Discussionmentioning
confidence: 98%
“…Treatment strategies in chronic aortic dissection should include occlusion of the FL. 4,[8][9][10][11][12] This early experience with the next-generation CP showed that positioning of the device in the FL is feasible, with minimal morbidity and mortality and a high rate of complete FL backflow cessation on the final angiogram and postoperative CTA. Compared with the earlier generation, the CP II is tubular and has no midsection, which creates a longer sealing zone.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, in 2018, an international, multicenter, non-randomized observational registry was initiated to gather data on patients with acute/ subacute Type B AD treated using the STABILISE technique, and this registry is still ongoing. Additional techniques have been proposed to achieve complete occlusion of the FL during endovascular treatment for aortic dissection (AD), such as the Knickerbocker and Candy-Plug techniques [30,31] . The Knickerbocker technique entails the placement of an oversized tubular stent-graft within the true lumen, followed by the rupture of the dissection membrane using a compliant balloon positioned at the midpoint of the graft.…”
Section: Managementmentioning
confidence: 99%
“…One such procedure following initial repair of the ascending aorta is the STABILISE technique with stentassisted balloon-induced intimal disruption and relamination of aortic dissection (AD) to improve their long-term outcomes in terms of aortic-related events [203]. Others comprise the use of homemade Candy Plugs [204], Candy Plug II [205,206], Coils and vascular plugs [207]. A systematic review of the literature on the intentional targeted false lumen occlusion after AD of Spanos et al revealed that intentional false lumen occlusion seems to be a feasible less invasive approach after TAAD or TBAD treatment, which is not broadly used [208].…”
Section: Novel Strategiesmentioning
confidence: 99%